Anti-epileptic and gut-protective effects of trioctanoin and the critical role of gut microbiota in a mouse model of epilepsy - Fei Yu; Jia-Lin Ji; Ying Wang; Yi-Di Liu; Yi-Mei Lian; Meng-Zhen Wang; Zheng-Xu Cai (Brain Research Bulletin)
Gut microbiota structure and function affect metabolism, gut health, and behavioral responses and are regulated by dietary factors. Recent research suggests the association of the gut-brain axis with epilepsy pathogenesis, thus offering potential new therapeutic targets. This study evaluated the anti-epileptic effect of trioctanoin and explored the potential role of the gut microbiota in a chronic pentylentetrazol (PTZ)-induced seizure mouse model. Behavioral assessments, electroencephalogram monitoring, immunofluorescence staining, neurotransmitter detection, gut microbiota sequencing, intestinal barrier function tests, and Fecal Microbiota Transplantation (FMT) were performed to systematically study the anti-epileptic effects of trioctanoin and the potential role of microbiota. Trioctanoin significantly restored glial cell proliferation to normal levels in chronic PTZ mice. Moreover, trioctanoin reduced elevated glutamate levels in the hippocampus of PTZ mice and improved gut microbiota imbalance and gut health by restoring the abundance of Dubosiella and Faecalibaculum genera, upregulating tight junction protein expression in the colon, and decreasing elevated levels of the inflammatory markers. Antibiotics(Abx) pre-treatment abolished the anticonvulsant protective effect of Trioctanoin. Although the FMT experiment did not transfer the anticonvulsant protection to the Abx+PTZ group mice, the results suggest that FMT still partially restored the gut microbiota imbalance in the chronic PTZ-induced epilepsy mouse model. These results provide new insights into dietary and gut microbiota-based therapeutic strategies for epilepsy.